Internal auditors in cooperatives organisation: with an overview of cooperatives organisation in the state of Kelantan / Mohd Zaky Awang Mat - Awang Mat, Mohd Zaky
A cooperative organisation is defined as an association of a group of peoples or both having as its main objective is to promote the economic interest of its members in accordance with the cooperative principles. This project paper concerned about the effectiveness of the internal auditors in cooperatives organisation in Kelantan. Internal auditor's function is to ensure the effectiveness of the system in the organization and it is one of the internal control device.